NARASI LIRIS FOTOGRAFI JURNALISTIK PADA MASA PANDEMI COVID-19: STUDI KASUS PROYEK FOTOGRAFI “STILL LIVES” OLEH THE NEW YORK TIMES - Purnomo, Aji Susanto Anom; Andrea, Novan Jemmi; Kusuma, Monica Revias Purwa (Jurnal Bahasa Rupa, 2021)
2020 is the year when the world is faced with a health crisis, namely the Covid-19 pandemic or also known as the Corona Virus. All aspects of life are affected by this crisis, the joints of humanity are faced with limitations. The mass media are intensively reporting various incidents regarding the Covid-19 pandemic. The stories are often accompanied by journalistic photos. One of the functions of photojournalism is to strengthen the story of what the media wants to convey. Journalistic photos during this pandemic usually feature scenes from medical activities, government policies and large narratives that are cold on empathetic human relations. However, different from most photojournalism in most mass media, The New York Times publishes "Still Lives" photography projects that are done by its photographers. The project presents a different narrative from this time of the pandemic. The “Still Lives” photography project is important because it presents journalistic photos that tell a domestic narrative that is close to the sides of universal humanity, namely the stories of the photographers' homes and families. This study aims to describe and interpret the “Still Lives” photography project as an alternative in creating a different narrative from photojournalism during the pandemic. This study used a descriptive qualitative research method based on phenomenology with Roland Barthes' main theory of semiotics and supported by journalistic photography theory and representation theory. The research results obtained a complete explanation and meaning of the “Still Lives” Project from The New York Times. The project according to the theory of photo journalistic is photo story based on personal experiences. From the analysis through the theory of semiotics from Roland Barthes and representation theory successfully obtained a result that basically projects “Still Lives” can be understood as a representation of the universal experience and feeling by mankind. Project “Still Lives” provides the representation of covid-19 pandemic through the mass media journalistic that show an alternative offer to journalistic practice to use lyrical narratives and personal experience in the story and more empathy in the mass publication of pandemic covid-19.